A multi-centre, parallel group superiority trial of silk therapeutic clothing compared to standard care for the management of eczema in children (CLOTHES Trial): study protocol for a randomised controlled trial. Issue 1 (December 2015) - Harrison, Eleanor; Haines, Rachel; Cowdell, Fiona; Sach, Tracey; Dean, Taraneh; Pollock, Ian; Burrows, Nigel; Buckley, Hannah; Batchelor, Jonathan; Williams, Hywel; Lawton, Sandra; Brown, Sara; et al.
Abstract Background Eczema is a chronic, itchy skin condition that can have a large impact on the quality of life of patients and their families. People with eczema are often keen to try out non-pharmacological therapies like silk therapeutic garments that could reduce itching or the damage caused by scratching. However, the effectiveness and cost-effectiveness of these garments in the management of eczema has yet to be proven. The CLOTHES Trial will test the hypothesis that 'silk therapeutic garments plus standard eczema care' is superior to 'standard care alone' for children with moderate to severe eczema. Methods/Design Parallel group, observer-blind, pragmatic, multi-centre randomised controlled trial of 6 months' duration. Three hundred children aged 1 to 15 years with moderate to severe eczema will be randomised (1:1) to receive silk therapeutic garments plus standard eczema care, or standard eczema care alone. Primary outcome is eczema severity, as assessed by trained and blinded investigators at 2, 4 and 6 months (using the Eczema Area and Severity Index (EASI)). Secondary outcomes include: patient-reported eczema symptoms (collected weekly for 6 months to capture long-term control); global assessment of severity; quality of life of the child, family and main carer; use of standard eczema treatments (emollients, corticosteroids applied topically, calcineurin inhibitors applied topically and wet wraps); frequency of infections; and cost-effectiveness. The acceptability and durability of the clothing will also be assessed, as will adherence to wearing the garments. A nested qualitative study will assess the views of a subset of children wearing the garments and their parents, and those of healthcare providers and commissioners. Randomisation uses a computer-generated sequence of permuted blocks of randomly varying size, stratified by recruiting hospital and child's age (< 2 years; 2 to 5 years; > 5 years), and concealed using a secure web-based system. The sequence of treatment allocations will remain concealed until randomisation and data collection are complete. Recruitment is taking place from November 2013 to May 2015, and the trial will be completed in 2016. Full details of results will be published in the National Institute for Health Research Journal series. Trial registration Current Controlled TrialsISRCTN77261365 (registered 11 November 2013).